Assessment of music education courses of public education center in the direction of the trainees opinions in the process of lifelong learning - CAN, AJDA AYLİN (ELSEVIER SCIENCE BV, 2012)
LifeLong Learning that came to the fore as an EU project in today's information age, in the process of the emergence of new education approaches, has become an emphasized topic in the field of education. Public Education Centers that provide service oriented towards the process of Lifelong Learning become crucial in terms of their contributions to personal and social development. In this context, this study aims to analyze the opinions of the music trainees in Kadikoy Public Education Center about the programs, education and the efficiency of the courses according to educational status and age variables. In the study, solution offers have been formed about what the rearrangements may be that the change necessitates.
Keywords: Life Long Learning; Public Education Center; Music Education